The influence of selected food ingredients on the reduction of the risk of endometriosis: a literature review - Mikut, Karolina; Gorajek, Anna; Bartoszewicz, Jakub; Nowakowska, Izabela; Wojtachnio, Dominika; Grądzik, Anna; Osiejewska, Aleksandra; Kudan, Małgorzata (Journal of Education, Health and Sport, 2022)
Endometriosis is a common disease that occurs in 6-10% of women of reproductive age. The disease is often associated with chronic pelvic pain and infertility. Endometriosis is an inflammatory disease and is estrogen dependent. Its definition is the presence of endometrial-like tissue outside the uterus. The etiology of the disease remains unclear. It is believed that a variety of immunological, genetic, hormonal, and environmental factors may be responsible for the development of endometriosis. Surgical confirmation of the presence of endometrial tissue outside the uterus is necessary for the diagnosis of endometriosis. For this reason, endometriosis is considered to be underdiagnosed. Currently, available treatments have many limitations and cause many side effects during their long-term use. For this reason, other treatment and prevention methods for this disease are being sought. Research on the influence of dietary factors on endometriosis allows concluding that diet and particular food ingredients can be considered a factor reducing the risk of endometriosis. Therefore, understanding the role of nutrition in the development of endometriosis is of great importance for the development of effective guidelines related to the prevention of this disease. Therefore, we have reviewed the available literature related to the impact of individual components of the daily diet on the risk of developing endometriosis. Omega-3 fatty acids, dairy products, and soy in particular appear to be promising dietary factors that could potentially reduce the risk of endometriosis. Further research is needed to solidify this knowledge.